Sex Psycoeducation to Prevent Sexual Harassment in Early Children at Paud Mawar, Sikka District - Sitti Anggraini; Epifania Margareta Ladapase; Monika Marganingsih Tunga; Maria Guntildis Nogo Tena (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
The number of cases of violence or abuse against children increases significantly every year. Because of that we need to immediately anticipate and find solutions, one of which is to do sex psychoeducation to prevent sexual abuse in early childhood. Psychoeducation of sex in early childhood aims to provide assistance to children as a form of learning and skills as well as preventive measures in tackling child sexual violence from an early age. The method used in this community service is the method of observation and interviews as well as psychoeducation. The results of community service show an increase in knowledge, before psychoeducation knowledge of early childhood about sex was 40%, after psychoeducation increased to 80%, there was a 40% increase in knowledge about sex education in early childhood